Komitmen Organisasional Dipengaruhi Kepemimpinan, Budaya Organisasi, dan Self-Efficacy - Rahmawati, Silvia; Korika Swasti, Ika (Jurnal Riset Pendidikan Ekonomi, 2025)
This study was conducted to analyze the influence of leadership, organizational culture, and self-efficacy on organizational commitment in government employees. This study used a quantitative approach, with purposive sampling or based on certain criteria. The number of respondents involved in this study was 76 Civil Servants at the Maritime Affairs and Fisheries Service obtained from the Slovin formula. Data collection was carried out through the distribution of questionnaires distributed online. Data analysis was carried out using the Partial Least Square (PLS) approach to determine the influence of each variable on organizational commitment. The results of the study indicate that (1) leadership has a positive and significant influence on organizational commitment, (2) organizational culture has a positive and significant influence on organizational commitment, and (3) self-efficacy also has a positive and significant influence on organizational commitment. These findings emphasize the importance of leadership development, strengthening organizational culture, and increasing self-efficacy to increase employee commitment. This study provides practical implications for human resource management in government agencies.